Comparison of Dried Blood Spot and Microtube Techniques for Trace Element Quantification by ICP-MS. Issue 2 (5th August 2022) - Perrais, Maïwenn; Thomas, Aurélien; Augsburger, Marc; Lenglet, Sébastien
Abstract: Microsampling techniques became more popular in the last decades, and their use for common analyses such as trace element quantification by inductively coupled plasma mass spectrometry (ICP-MS) has been investigated. We decided to compare two of these techniques (dried blood spots and microtubes) to evaluate their potential for the analysis of 12 trace elements in human whole blood: aluminum (Al), total arsenic (As), cadmium (Cd), cobalt (Co), chromium (Cr), copper (Cu), manganese (Mn), molybdenum (Mo), nickel (Ni), lead (Pb), selenium (Se) and zinc (Zn). Signal contributions from blank filter paper and instability at room temperature for several elements in the dried blood spot samples restrained our enthusiasm for the use of this technique. Conversely, microtube samples presented low background contamination and good stability under different temperature conditions. Therefore, our results demonstrate that the use of microtubes is more suitable than dried blood spots for trace element quantification in human blood, both in research and routine analysis.